2022
DOI: 10.3390/biology11020154
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Yield and Cryosurvival of Spermatozoa from Rhinoceros Ejaculates Using the Enzyme Papain

Abstract: The preservation of rhinoceros semen is vital for captive breeding programs. While successful collection and cryopreservation of rhinoceros semen has been reported, the volume and quality of semen produced is often low due to the high viscosity associated with ejaculates collected via electroejaculation. Reducing semen viscosity would enable access to previously unusable spermatozoa from viscous fractions and could improve quality post-thaw. The enzyme papain successfully reduced the viscosity of camelid semen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…It is yet unclear how papain works to enhance the quality of the camel semen that is collected. Rickard et al (2022) consider that semen viscosity is not related to the volume of plasma generated but to the inclusion or amount of a particular protein. Previous studies in alpaca have shown that papain targets glycosylated proteins within the seminal fluid instead of glycosaminoglans (Kershaw et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is yet unclear how papain works to enhance the quality of the camel semen that is collected. Rickard et al (2022) consider that semen viscosity is not related to the volume of plasma generated but to the inclusion or amount of a particular protein. Previous studies in alpaca have shown that papain targets glycosylated proteins within the seminal fluid instead of glycosaminoglans (Kershaw et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In camelids, glycoproteins released by the bulbourethral glands are responsible for the trapping of spermatozoa within the camelid uterus (Apichela et al., 2014). It is highly probable that papain, by focusing on glycoproteins, decreased the viscosity of ejaculates (Rickard et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the value of spermatozoa acrosomal integrity in our study was relatively high compared to several species that had been previously reported. The percentage of post-thaw acrosomal integrity in rhinos was reported to be 80.00% [ 49 ] and 68.00% [ 53 ], whereas in bison it was 71.13%–76.56% [ 54 ]. Here, we also noticed that spermatozoa acrosomal integrity in both samples used in our study showed a considerably high percentage regardless of the low post-thaw spermatozoa motility and viability.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa cryopreservation is an example of just one ART that can facilitate a living cryobank capable of aiding in the genetic management of endangered species and has been achieved in many species (covered in-depth elsewhere, for example, amphibians: Browne et al 2019 ; fish: Asturiano et al 2017 , Xin et al 2017 ; mammals: Swanson et al 2007 , Rickard et al 2022 ; avians: Asano & Tajima 2017 , Cardoso et al 2020 ). Storing genes in the form of spermatozoa is particularly beneficial as spermatozoa are continuously replenished haploid cells that can be collected from numerous genetically diverse representatives of a species.…”
Section: Gamete and Reproductive Tissue Cryopreservationmentioning
confidence: 99%